USING TACHIYOMI METHOD IN TEACHING ENGLISH READING FOR VOCATIONAL STUDENT - Eska Perdana Prasetya (ENGLISH, 2018)
Teaching English for Vocational School, especially teaching reading is not easy. The teachers have to deal with the students who have the different characteristics on the class. Reading is also the other problems for vocational students. They feel hard to read. Knowing the characteristics and factors that cause difficulty in reading for vocational students, the teachers have to poses creative and effective method to teach English for vocational student. In Japan, one of the methods for teaching English reading for vocational student is tachiyomi method. This research employed survey method to know the improvement of student English reading skill using tachiyomi method. From the test, it showed that the average of all aspect; main idea, specific information, reference, inference, and vocabulary in every meeting, in each cycle had improved. The result of the observation also showed that there were improvement of students’ participations and students’ attitudes in every meeting.